De Lélia Gonzalez a Marielle Franco : mulheres negras e seus processos comunicacionais interseccionais de resistência - Pâmela Guimarães da Silva (2021)
The purpose of this doctoral thesis is to apprehend the arrangements created and the interactional strategies used by black women in their political insurgencies to transform the social place of their peers. Therefore, we are mainly affiliated with Sueli Carneiro theory (2005) that Brazilian society is structured under the raciality device, which, ultimately, has genocide and black epistemicide as objectives. However, we also observe that, continuously, black subjects rearrange the elements that make up the device and create spaces of resistance to its effects. Especially black women. With that in mind, we undertake a historical and analytical retreat in order to identify the communicational practices that black women have been undertaking to transform this reality that inscribes black subjects under the sign of death (factual and symbolic). Based on a methodology that we call the arc of life — which, inspired by the stylistic resource of the writer Conceição Evaristo in her work Olhos d'água, consists of presenting a significant group of women, with multiple characteristics and experiences, but which if observed together, could form an arc of life any black woman — we selected as our corpus: the column Negra, written by Lélia Gonzalez (1980); the column Mulher Negra e Pequim 95 - da Informação à Ação written by members of the Geledés Institute (1990); the column Opinião of Correio Braziliense newspaper, reproduced in Portal Geledés (2000), written by Sueli Carneiro; the opinion articles by Djamila Ribeiro in Blogueiras Negras (2010) and the article Últimas palavras by Marielle Franco (2018). Our approach to this material revealed that these women needed and continually need to destabilize the raciality device, which is manifested through a certain discursive authorization that creates legibilities, while imprisoning them in the social place of silencing. To do so, they create symbolic territories (online and offline), in which: 1) they define and evaluate themselves; 2) expose the interconnected nature of the oppressions that affect them and 3) value the culture itself. In other words, they carry out procedures of subjectivation and political emancipation — a recognition of themselves, different from the regulations of the raciality device. As all these dimensions of subjectivation and emancipation take race as a reference, but produce interactions whose meanings are different from those produced by the raciality device, our hypothesis is that these women constantly try to modify the arrangement of the elements that make up the device of raciality, so that they position themselves under an intersectional perspective and the interactions that occur in their environment no longer produce annihilation. It is a continuous attempt to engender in brazilian society an intersectional dispositional arrangement (BRAGA, 2018, 2020) of resistance to the racial device that will shape and guide interactions. A kind of against-device that manifests itself: with the entry into the order of discourse as columnists, in the organization and publication of their own demands, in the rescue and publication of their own history, in the exposure of oppressive social engineering, in the appreciation of their own culture, in the act of self-defining and self-evaluating.